EFEK HEPATOPROTEKTOR ANDROGRAPHOLIDE TERHADAP AKTIVITAS ALANIN AMINOTRANSFERASE DALAM SERUM Rattus norvegicus JANTAN GALUR WISTAR YANG DIINDUKSI KARBON TETRAKLORIDA - Dewinta Putri Utami; Andriani Andriani; Mardhia Mardhia; Virhan Novianry; Mistika Zakiah (Faculty of Pharmacy, Universitas Muslim Indonesia, 2021)
Background: Andrographolide is a diterpenoid bioethanol that effectively prevent liver injury by reducing liver oxidative stress response. Method : The research was randomized experimental design with pretest-posttest design. Thirty male wistar rats was randomly divided into 6 groups, normal control, negative control (0,2 ml CCl4), and positive control (500 mg/kgBW curcumin), dose I (50 mg/kgBW), dose II (100 mg/kgBW), dose III (200 mg/kgBW) given for 8 days and induced by 0,2 ml CCl4 on the first day. Data was analyzed by One-Way Anova test, LSD Post-Hoc test and paired T test. Results :All groups induced by CCl4 shows elevated of ALT activity. The posttest results shows significant differences of ALT activity between groups (p<0,05). Conclusion : Andrographolide shows hepatoprotector effect by decrease the activity of ALT in male wistar rats induced by CCl4. The effective dose of andrographolide is 200 mg/kgBW.